Inter-core Crosstalk Dependence on Design Parameters in Coherent Detection Weakly-Coupled Multicore Fiber Systems - Pinheiro, B.; Rebola, J.; Cartaxo, A. (ICTON 2018 - 20th International Conference on Transparent Optical Networks, 2018)
We assess, through numerical simulation, the dependence of the variance of the inter-core crosstalk (ICXT) and the maximum allowable ICXT level on the design parameters of coherent detection MCF systems. The analysed design parameters are the order of the quadrature amplitude modulation (QAM) signals, roll-off factor, time misalignment between the signal in different cores and skew between cores. The results show that, when the roll-off factor is 0, the maximum allowable ICXT level is independent of the skew and decreases for higher QAM orders. For a roll-off factor of 1, the maximum allowable ICXT level depends on the skew and time misalignment of core signals. In this case, the maximum allowable ICXT level increases by 3.6 dB relative to the case of roll-off factor of 0 with null skew, and by 2 dB, when the skew is much higher than the symbol period.